2020
DOI: 10.21203/rs.3.rs-16120/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the stone-free rates of mini-percutaneous nephrolithotomy, standard percutaneous nephrolithotomy, and retrograde intrarenal surgery for renal stones: A systematic review and network meta-analysis

Abstract: Background: Retrograde intrarenal surgery (RIRS) and percutaneous nephrolithotomy (PCNL) are performed to treat renal stones. PCNL is effective for kidney stones >2 cm but is invasive compared with RIRS. Miniature PCNL (mPCNL) has been used as an alternative treatment for conventional PCNL, and employs a miniature endoscope of 11–18 Fr. We conducted a systematic review of published studies regarding the RIRS, PCNL, and mPCNL treatment modalities, and performed a network meta-analysis of the success or stone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A comparative study of Mini-PCNL versus Conventional PCNL showed no difference in stonefree rate (SFR) 9 . Moreover, a meta-analysis by Wei Zhu and colleagues concluded that Mini-Percutaneous Nephrolithotomy resulted in less bleeding, fewer transfusions, reduced need for nephrostomy with lesser pain, and shorter hospitalization 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study of Mini-PCNL versus Conventional PCNL showed no difference in stonefree rate (SFR) 9 . Moreover, a meta-analysis by Wei Zhu and colleagues concluded that Mini-Percutaneous Nephrolithotomy resulted in less bleeding, fewer transfusions, reduced need for nephrostomy with lesser pain, and shorter hospitalization 10 .…”
Section: Introductionmentioning
confidence: 99%